Separation of isomers of chiral thiourea derivatives via spontaneous resolution and rationale of molecular recognition - Dwivedi, Astha M.; Gonnade, Rajesh G.; Sahoo, Suban K.; Bedekar, Ashutosh V. (CrystEngComm, 2025)
Enrichment of enantiomers during crystallization of racemic thiourea derivatives was investigated. The spontaneous resolution of a chiral thiourea derivative via preferential crystallization is attributed to thermodynamic stability when molecules of identical chirality bind with each other in the crystal lattice. Single crystal X-ray analysis reveals the interactions responsible for self-recognition of molecules of the same chirality in the unit cell. The tendency of the thiourea derivative to form a conglomerate is supported by IR spectroscopy, thermal analysis and computational studies.